Strategi Pesan Promosi, Motivasi Diri, dan Pengambilan Keputusan Adopsi Inovasi Kursus Online - Putri, Priscilla Perdana; Murwani, Endah; Astagini, Nuria (Universitas Prof. Dr. Moestopo (Beragama), 2024)
This study is motivated by the development of innovative training institutions such as Skill Academy, which offers online self-development courses. Through Instagram, Skill Academy promotes its products, services, and product benefits. The success of adopting an innovation is also influenced by consumers during the decision-making process. Motivation is one of the driving factors behind an individual’s decision to adopt online courses. The purpose of this study is to determine the influence of promotional message strategies on Instagram and self-motivation on the decision to adopt Skill Academy. The concepts used in this research include promotional message strategies, self-motivation, and consumer decision-making. The research approach is quantitative, employing a survey method. Data collection was conducted using a questionnaire with a sample size of 150 followers of the Skill Academy Instagram account. The hypothesis testing in this study utilized Multiple Linear Regression Analysis. The results of the study indicate that promotional message strategies on Instagram and self-motivation contribute 55% to the decision to adopt Skill Academy online courses. Partially, promotional message strategies on Instagram significantly influence the decision to adopt Skill Academy online courses, as does self-motivation. Promotional message strategies on Instagram and consumer motivation simultaneously have a significant impact on decision-making.